Freight Train Scheduling using Integer Linear Programming: A case study of cement distribution - Rachmawati, Nur Layli; Putri, Dian Permana (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
Transportation process is responsible for providing efficiency of moving products considering time, cost, and vehicle utilities through inbound and outbound logistics. Transportation disruptions such as congestion, delays, or cancellations can have a detrimental impact on the company. PT X uses trains to transport unpackaged cement in bulk from factory to port. PT X has not met the daily train delivery target due to train delays, inconsistency delivery frequency and ineffective schedule. Therefore, the quantity of shipment does not meet the expected target. In this study, optimization of train rescheduling was carried out to minimize total train delays. This optimization is expected to be able to create a new train schedule that meets the daily delivery target. The proposed model is formulated as and solved as Integer Linear Programming (ILP) problem by considering single-track railway constraints. Results show the optimal train schedules give a total delay of 26 minutes. Compared to the existing condition, train delays are reduced by 69.7% and provide a more effective schedule with consistent delivery frequency.